2015
DOI: 10.1371/journal.pone.0145075
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose Levels Correlate with Disease Severity of Guillain-Barré Syndrome

Abstract: ObjectiveA potential association between diabetes and Guillain-Barré syndrome (GBS) has been indicated by a few case studies. We retrospectively analyzed the clinical features of a large cohort of GBS patients to explore the relationship between the level of fasting plasma glucose (FPG) obtained in the acute phase at admission and the severity of GBS.MethodsThree hundred and four GBS patients were divided into two groups, one with normal FPG and the other with high FPG levels according to the international sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Although the enhanced glycolysis has been reported in systemic lupus erythematosus (SLE) [ 11 ] and autoimmune arthritis [ 12 , 13 ], up to now, no research about the metabolic reprogramming in GBS or EAN can be found. Considering the hypermetabolism and remarkable weight loss in GBS patients [ 14 ] and the fact that fasting glucose levels correlate with the disease severity of GBS [ 15 ], it is plausible to assume that enhanced glycolysis exists and contributes to the pathogenesis of GBS. Thus, we explored the roles of glycolysis in the classic model of EAN with a well-known glycolysis inhibitor, 2-deoxy- d -glucose (2-DG) [ 10 , 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the enhanced glycolysis has been reported in systemic lupus erythematosus (SLE) [ 11 ] and autoimmune arthritis [ 12 , 13 ], up to now, no research about the metabolic reprogramming in GBS or EAN can be found. Considering the hypermetabolism and remarkable weight loss in GBS patients [ 14 ] and the fact that fasting glucose levels correlate with the disease severity of GBS [ 15 ], it is plausible to assume that enhanced glycolysis exists and contributes to the pathogenesis of GBS. Thus, we explored the roles of glycolysis in the classic model of EAN with a well-known glycolysis inhibitor, 2-deoxy- d -glucose (2-DG) [ 10 , 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated levels of glucose and the ketone body are a typical clinical symptom in diabetics. Hyperglycemia and ketoacidosis have been reported in blood of GBS patients 26–29 , but it has not been reported that this clinical finding also manifests in the CSF metabolome. On contrary, decreased glucose content was observed in IDDs.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent study, diabetes mellitus type 2 was present in 32% of 85 patients with acute polyradiculoneuropathy, and 3‐month prognosis was worse in patients with GBS and diabetes (Bae et al, ) . Higher fasting plasma glucose in the acute phase of GBS correlated with worse motor, autonomic and respiratory deficit and may predict the short‐term prognosis of GBS (Wang et al, ) . There are no other studies about GBS and diabetes mellitus, except for case reports (Wang et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…Higher fasting plasma glucose in the acute phase of GBS correlated with worse motor, autonomic and respiratory deficit and may predict the short‐term prognosis of GBS (Wang et al, ) . There are no other studies about GBS and diabetes mellitus, except for case reports (Wang et al, ) . In line with these findings, diabetes mellitus may cause worsening of other neuropathies such as hereditary motor and sensory neuropathy (Sheth et al, ) .…”
Section: Discussionmentioning
confidence: 99%